UPAYA MENINGKATKAN PENGUASAAN MATERI LOGARITMA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE PADA SISWA KELAS X SMA NEGERI 1 SUNGAI RAYA - Rufini, Rufini (Universitas Tanjungpura, 2013)
Efforts to improve themastery of logarithm through cooperative learning model think pair shareatclass X students of SMA Negeri 1 Sungai Raya . The purpose of this study was to describe the effort to improve the mastery of logarithm through cooperative learning model think pair share in class X SMA Negeri 1 Sungai Raya . The method used was Classroom Action Research conducted by 2 cycles with a purpose to get good study planning, implementation and up can improve result learn student in comprehending logarithm items at study of mathematics. With the descriptive method of data collector that is used is a matter of observation and test sheets . Result of from this research is from condition of early to condition of first cycleÂ its improvement equal to 19,8 %, and from condition of first cycle to condition of second mount equal to 13,3%. Becoming from condition of early to condition of second mount equal to 35,7 %. This means that there has been a increasedthe mastery of logarithm through cooperative learning model think pair shareatclass X students of SMA Negeri 1 Sungai Raya. Keywords: Improve math skills,material logarithm, cooperative learning model think pair share.